1998
DOI: 10.1023/a:1011919319810
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This study demonstrates that L-amino acid-nucleoside chimeras can serve as prodrugs to enhance intestinal absorption via the PEPT1 transporter, providing a novel strategy for improving oral therapy of nucleoside drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
97
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(101 citation statements)
references
References 25 publications
3
97
1
Order By: Relevance
“…While BPHL has relatively high K m values, it exhibits a catalytic efficiency comparable to that of carboxylesterase against some widely used synthetic substrates (28 (10) demonstrated that more than 90% of the drug in the receiver compartment was ACV rather than the prodrug, indicating extensive intracellular VACV hydrolysis during cellular transport. This result suggests that one or more VACV-hydrolyzing enzymes, including BPHL in Caco-2 cells, are efficient at hydrolyzing VACV during mucosal cell transport.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While BPHL has relatively high K m values, it exhibits a catalytic efficiency comparable to that of carboxylesterase against some widely used synthetic substrates (28 (10) demonstrated that more than 90% of the drug in the receiver compartment was ACV rather than the prodrug, indicating extensive intracellular VACV hydrolysis during cellular transport. This result suggests that one or more VACV-hydrolyzing enzymes, including BPHL in Caco-2 cells, are efficient at hydrolyzing VACV during mucosal cell transport.…”
Section: Discussionmentioning
confidence: 99%
“…The HPLC system consisted of a reversed-phase column (Ultrasphere, C-18, 5 m, 4.6 ϫ 250 mm, Beckman), Waters 515 pump; 996 Photodiode Array UV detector; and WISP model 712 autosampler (Waters, Milford, MA). The remaining prodrugs D/L-valacyclovir (D-VACV, VACV), glycyl ester acyclovir (Gly-ACV), and L-valyl ester AZT (Val-AZT) and production of parent drugs were assayed by HPLC as previously described (10). Briefly, prodrugs and their parent drugs except VGCV were separated and eluted by 2-8% acetonitrile in 40 mM ammonium formate buffer, pH 3.5, at a flow rate of 1 ml/min with detection at 254 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Involvement of PEPT1 may explain the difference in bioavailability between valacyclovir (PEPT1 substrate) and acyclovir (non-substrate) in humans. 5,6) We have recently reported that rab8-null mice, which exhibit minimal expression of PEPT1 on apical membranes of small intestine, lack saturable uptake of a prototypical PEPT1 substrate glycylsarcosine (Gly-Sar).7) This may indicate a predominant role of PEPT1 in the peptide absorption. In addition to small intestine, PEPT1 is functionally expressed in some human cancer cell lines [8][9][10] and therefore would be a promising target for tumor detection.…”
mentioning
confidence: 99%
“…[7][8][9] Enhanced bioavailabilities of the amino acid prodrugs is attributed to carrier mediated intestinal absorption via intestinal transporters such as a human peptide transporter hPept1 or an amino acid transporter ATB 0,ϩ . 4,[10][11][12] Nucleoside antiviral and anticancer agents are important class of drugs for the fight against viral diseases and cancer. However, they often exhibit poor pharmaceutical and absorption, distribution, metabolism and excretion (ADME) properties.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] Valine prodrugs of acyclovir and ganciclovir, valacyclovir and valganciclovir, respectively, exhibit 3-5 times higher systemic exposure than the parent compounds. [7][8][9] Enhanced bioavailabilities of the amino acid prodrugs is attributed to carrier mediated intestinal absorption via intestinal transporters such as a human peptide transporter hPept1 or an amino acid transporter ATB 0,ϩ .…”
mentioning
confidence: 99%